Calcium carbonate-conjugated polymer composite nanoparticles with anti-tumor and anti-metastasis effects and their application

By rupturing the calcium carbonate-conjugated polymer composite nanoparticles in a weakly acidic environment of tumors, releasing Ca2+ and conjugated polymers, combining photodynamic therapy and calcium overload mechanism, the side effects of existing cancer treatment on normal cells and tumor metastasis problems are solved, and efficient comprehensive cancer treatment is achieved.

CN116920090BActive Publication Date: 2025-08-08SHAANXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310893463.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-20
Publication Date
2025-08-08
Estimated Expiration
2043-07-20

AI Technical Summary

Technical Problem

Existing cancer treatment methods have negative effects on normal cells, and cancer metastasis is difficult to effectively inhibit. Traditional nanoplatforms have great side effects in tumor treatment, and the role of calcium ions in tumor cells has not been fully utilized.

Method used

A calcium carbonate-conjugated polymer composite nanoparticles were developed to encapsulate the conjugated polymer through calcium carbonate nanosphere shells, and rupture the tumor's weak acidic environment to release Ca2+ and conjugated polymers. Combined with photodynamic therapy and calcium overload mechanisms, they jointly kill tumor cells and inhibit metastasis.

Benefits of technology

It achieves efficient anti-tumor and anti-metastasis effects, significantly reduces tumor volume, inhibits tumor cell migration, and has good biocompatibility and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116920090B_ABST
    Figure CN116920090B_ABST
Patent Text Reader

Abstract

The present invention discloses a calcium carbonate-conjugated polymer composite nanoparticle with anti-tumor and anti-metastasis effects and its application. The nanoparticles rupture and decompose in the weakly acidic microenvironment of the tumor, releasing the conjugated polymer and a large amount of Ca 2+ The conjugated polymer can generate reactive oxygen species or heat energy to kill tumor cells under light. In addition, reactive oxygen species can also put tumor cells in a state of high oxidative stress, causing mitochondrial dysfunction and desensitization of calcium ion-related channels, causing intracellular "calcium overload" and inducing tumor cell death. These multiple effects make the nanoparticles highly effective in cancer treatment. Extracellular Ca 2+ Increased levels can enhance the adhesion between tumor cells by regulating the morphology of cadherin, thereby inhibiting tumor cell migration. In this invention, the calcium carbonate-conjugated polymer composite nanoparticles have excellent anti-tumor and anti-metastasis effects, providing a new approach for the comprehensive treatment of cancer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cancer treatment and relates to calcium carbonate-conjugated polymer composite nanoparticles with anti-tumor and anti-metastasis effects. Background Art

[0002] The incidence of cancer in my country continues to rise, and cancer has become one of the main threats to human health. At present, the main treatments for cancer are surgical intervention, chemotherapy, and radiotherapy. However, chemotherapy and radiotherapy usually have negative effects on normal cells, leading to serious side effects such as neuropathy, neutrophilia, and renal failure; surgery can remove the primary tumor, but it cannot completely remove micrometastases that invade adjacent tissues or spread to distant sites, and there is a greater risk of postoperative recurrence and metastasis. It is reported that cancer metastasis is the main cause of cancer-related deaths. Curing tumor metastasis remains one of the biggest challenges in cancer treatment. Therefore, there is an urgent need to develop more efficient cancer treatment strategies with metastasis inhibition effects.

[0003] In recent years, multifunctional nanoplatforms with comprehensive diagnostic and therapeutic functions have greatly promoted the development of cancer treatment. Among them, stimulus-responsive (pH, redox gradient and enzyme concentration changes) nanoplatforms have attracted widespread attention. Compared with traditional non-responsive nanoplatforms, activatable nanoplatforms can not only accurately treat at the expected time and location (such as only at the lesion), but also reduce side effects on normal tissues. Therefore, the development of activatable nanoplatforms with good biocompatibility is of great significance in the field of cancer nanomedicine. Calcium, as the fifth most abundant element in the earth's crust, is an essential mineral nutrient for organisms. In addition, calcium ions (Ca 2+ ) is known as the second messenger in cells, which is related to a variety of biochemical signal transduction pathways in cells and plays a key role in a variety of physiological processes such as cell proliferation, metastasis and apoptosis. More and more studies have shown that Ca 2+ Disturbances in Ca2+ can cause cytotoxicity and trigger cell death. For example, in tumor cells, Ca2+ 2+ Abnormally elevated levels lead to oxidative stress, becoming an important pro-apoptotic factor for tumor cells. Synthetic calcium-based (CaXs) biomaterials, especially CaCO3 nanoparticles, can decompose into Ca in the weakly acidic environment of tumors. 2+ Calcium-based biomaterials have been widely studied in the biomedical field due to their advantages of high drug loading rate, excellent biocompatibility, and ease of preparation and functionalization. However, the calcium-based biomaterials reported so far are often used as nanocarriers to load chemotherapy drugs, and during the treatment process, calcium 2+ The effect of Ca content on tumor cells is often overlooked. Therefore, calcium carbonate nanoparticles are used as carriers to disrupt the Ca content in tumor cells. 2+Homeostasis is expected to become a potential anti-tumor treatment.

[0004] Photodynamic therapy (PDT) is a widely used non-invasive tumor treatment technology that relies on photosensitizers to convert light energy into cytotoxic reactive oxygen species (ROS), which damage or kill cells by disrupting cell membrane structure or inhibiting enzyme activity. Compared with traditional treatments, PDT offers unique advantages such as high efficiency, minimal side effects, and low drug resistance. Conjugated polymers (CPs) have advantages such as high fluorescence quantum yield, excellent photostability, good biocompatibility, easy side chain modification, and low cost, and are increasingly being used in biosensing, cell imaging, and drug delivery.

[0005] Based on the above research, the development of a CaCO3 multifunctional nanoplatform with multiple anti-tumor effects and the ability to inhibit tumor cell metastasis can effectively alleviate the problems of low therapeutic efficiency, poor biosafety and high risk of cancer metastasis of current treatment methods, and provide new ideas for the comprehensive treatment of cancer. Summary of the Invention

[0006] The purpose of the present invention is to provide a calcium carbonate-conjugated polymer composite nanoparticle with good and efficient anti-tumor and anti-metastasis effects. The calcium carbonate shell of the nanoparticle breaks and decomposes in the weakly acidic environment of the tumor, and the released Ca 2+ The conjugated polymers can effectively kill tumor cells through the synergistic effect of PDT and calcium overloading, and can also increase extracellular Ca 2+ Regulate the level of E-cadherin on the tumor cell membrane to inhibit the shedding and metastasis of tumor cells.

[0007] To achieve the above objectives, the present invention employs a technical solution: encapsulating a conjugated polymer with calcium carbonate nanoshells and modifying the nanoshells with liposomes to form calcium carbonate-conjugated polymer composite nanoparticles. The calcium carbonate-conjugated polymer composite nanoparticles have a particle size of 30 to 200 nm.

[0008] The above conjugated polymer is Any one of the following, wherein n represents the repeating unit of the monomer in the conjugated polymer, and the number average molecular weight of the conjugated polymer is 10,000 to 50,000; R is selected from Any one of, m is an integer of 1 to 19, R1 represents CH3, OCH3, Br, COOCH3, Any one of, p is an integer from 1 to 6; R' is selected from H, Any one of the following, q is an integer from 1 to 19, R2 is selected from Br or CH3; and Z is selected from CH or N.

[0009] The above conjugated polymer It is composed of monomers and monomer It is generated by Sonagashira coupling reaction, wherein X represents I or Br.

[0010] The above conjugated polymer It is composed of monomers and monomer It is generated by Sonagashira coupling reaction, wherein X represents I or Br.

[0011] The above conjugated polymer It is composed of monomers and monomer Generated by Suzuki coupling reaction.

[0012] The above conjugated polymer It is composed of monomers and monomer Generated by Suzuki coupling reaction.

[0013] The preparation method of calcium carbonate-conjugated polymer composite nanoparticles of the present invention comprises the following steps:

[0014] (1) Containing Ca 2+ The conjugated polymer mixed solution and ammonium bicarbonate were placed in beakers respectively and placed in a vacuum drying oven. The temperature was raised to decompose the ammonium bicarbonate into CO2 and NH3. The CO2 was then diffused into the Ca in the solution. 2+ The reaction generates a hollow calcium carbonate nanoshell, which encapsulates the conjugated polymer to obtain calcium carbonate nanoparticles encapsulating the conjugated polymer; the calcium carbonate nanoparticles containing Ca 2+ The conjugated polymer mixed solution is obtained by dissolving calcium chloride, conjugated polymer and dopamine hydrochloride in anhydrous ethanol.

[0015] (2) Calcium carbonate nanoparticles encapsulating conjugated polymers were ultrasonically dispersed in ethanol, and then a chloroform solution of 1,2-dioleoyl-sn-glycero-3-phosphate (sodium salt) (DOPA) was added. The mixture was ultrasonically dispersed for 15 to 30 minutes, and the unbound DOPA was removed by centrifugation. The nanoparticles were then dispersed in chloroform, and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC), cholesterol, and distearoylphosphatidylethanolamine-polyethylene glycol 3400 (DSPE-PEG) were added. 3400 ), stirred for 12 to 15 hours in the dark, and after removing the chloroform, the nanoparticles were dispersed with tetrahydrofuran, added to secondary water under ultrasonic action, and ultrasonicated for 15 to 30 minutes to fully hydrate it. Finally, the residual tetrahydrofuran was removed to obtain calcium carbonate-conjugated polymer composite nanoparticles.

[0016] In the above step (1), the mass ratio of the calcium chloride, the conjugated polymer and the dopamine hydrochloride is preferably 300:10-20:1-5.

[0017] In the above step (1), it is further preferred to raise the temperature to 30-60°C to decompose the ammonium bicarbonate into CO2 and NH3, and react for 5-20 hours to allow the CO2 to react with the Ca in the solution. 2+ The reaction generates hollow calcium carbonate nanoshells that encapsulate the conjugated polymer.

[0018] In the above step (2), preferably the DOPA, DPPC, cholesterol and DSPE-PEG 3400 The molar ratio of DOPA is 1-3:3:1-4:1-3, wherein the mass ratio of DOPA to the conjugated polymer in the calcium carbonate nanoparticles encapsulating the conjugated polymer is 4:15-22.

[0019] The present invention uses calcium carbonate-conjugated polymer composite nanoparticles in the preparation of anti-tumor and anti-tumor metastasis drugs. Its mechanism of action is: calcium carbonate-conjugated polymer composite nanoparticles reach the tumor site through the EPR effect, and under the influence of the weakly acidic environment of the tumor, the nanoparticles rupture and release the conjugated polymer and Ca 2+ When irradiated with white light, the conjugated polymers released by the nanoparticles will generate a large amount of ROS, achieving PDT treatment; the ROS generated at the same time put the cells in a state of oxidative stress, leading to abnormal mitochondrial membrane potential, desensitization of calcium ion-related channels, and ultimately causing intracellular calcium overload, resulting in calcification and inducing cell death. In addition, the Ca generated by the nanoparticles when they rupture and decompose outside the tumor cells 2+ Can fully bind to the Ca between the repeating units of the cadherin polypeptide chain 2+ The site binding maintains the cadherin polypeptide chain in a rigid rod-shaped dimer form, greatly increasing the adhesion between tumor cells and thus inhibiting the shedding and metastasis of tumor cells. This calcium carbonate-conjugated polymer composite nanoparticle not only achieves multimodal tumor treatment such as photodynamic therapy, mitochondrial dysfunction, and cell calcification, but also effectively inhibits tumor cell metastasis, demonstrating a highly effective and excellent comprehensive cancer treatment effect.

[0020] The beneficial effects of the present invention are as follows:

[0021] (1) The calcium carbonate-conjugated polymer composite nanoparticles of the present invention can achieve highly effective cancer treatment effects through the synergistic effects of photodynamic therapy, mitochondrial dysfunction, and calcium overload. Under light conditions, when the conjugated polymer content in the nanoparticles was 4 μM, the viability of breast cancer MCF-7 cells dropped to 3%, significantly higher than the effects of photodynamic therapy or calcium overload therapy alone. In animal model experiments, the tumor volume of tumor-bearing mice was essentially reduced to zero after five treatments, significantly inhibiting the growth of tumor volume in tumor-bearing mice.

[0022] (2) In addition to having anti-tumor effects, the calcium carbonate-conjugated polymer composite nanoparticles of the present invention can also regulate extracellular Ca 2+ The nanoparticles inhibited the migration of breast cancer cells 4T1 and MCF-7 by 96.6% and 87.4%, respectively. Following treatment, 4T1 tumor-bearing mice showed minimal or no significant metastatic nodules in their lungs.

[0023] (3) The calcium carbonate-conjugated polymer composite nanoparticles of the present invention have good biocompatibility. Under dark conditions, the nanoparticles showed low cytotoxicity to breast cancer MCF-7 cells. In animal tests, mice gained weight slightly during the 20-day treatment process and did not experience significant weight loss. No obvious pathological changes were observed in the main organs of the mice, and their structural morphology was normal, demonstrating that the nanoparticles still have good biosafety in vivo. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a microscopic morphology of the calcium carbonate-conjugated polymer composite nanoparticles prepared in Example 1.

[0025] Figure 2 The calcium carbonate-conjugated polymer composite nanoparticles prepared in Example 1 were Ca 2+ Release curve over time.

[0026] Figure 3 The killing effects of the calcium carbonate-conjugated polymer composite nanoparticles prepared in Example 1 and the conjugated polymer or calcium carbonate nanoparticles alone on MCF-7 cells are shown.

[0027] Figure 4 This is a quantitative graph showing the inhibitory effect of calcium carbonate-conjugated polymer composite nanoparticles prepared in Example 1 on tumor cell metastasis with increasing concentration; wherein a is a graph showing the migration rate of MCF-7 cells changing with concentration, and b is a graph showing the migration rate of 4T1 cells changing with concentration.

[0028] Figure 5 This is a quantitative graph showing the inhibitory effect of calcium carbonate-conjugated polymer composite nanoparticles prepared in Example 1 on tumor growth in 4T1 tumor-bearing mice.

[0029] Figure 6 This is a quantitative graph showing the inhibitory effect of the calcium carbonate-conjugated polymer composite nanoparticles prepared in Example 1 on lung metastasis in 4T1 tumor-bearing mice. DETAILED DESCRIPTION

[0030] The present invention is described in detail below with reference to the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0031] Example 1

[0032] The calcium carbonate-conjugated polymer composite nanoparticles of the present embodiment are based on the conjugated polymer PFV-COOH as the core, wrapped in a calcium carbonate nanoshell, and then modified with liposomes on its surface to form the final calcium carbonate-conjugated polymer composite nanoparticles PFV-COOH / CaCO3 / PDA@PEG. The specific synthesis process is as follows: 300mg of calcium chloride dihydrate, 20mg of conjugated polymer PFV-COOH and 2mg of dopamine hydrochloride (PDA) are added to a beaker filled with 200mL of anhydrous ethanol and stirred to dissolve, the beaker mouth is wrapped with aluminum foil and pierced, and then the beaker is placed in a vacuum drying oven containing 20g of NH4HCO3 and reacted at 40°C for 10h. After the reaction is completed, the precipitate is collected by high-speed centrifugation (8000rpm, 10min), and the resulting precipitate is calcium carbonate nanoparticles encapsulating the conjugated polymer. The precipitate was ultrasonically dispersed in 2 mL of ethanol, and 2 mL of 2 mg / mL (0.006 mmol) DOPA chloroform solution was added and ultrasonication was continued for 20 min. Unbound DOPA was removed by centrifugation and the precipitate was dispersed in chloroform again. 8 mg (0.01 mmol) DPPC, 4 mg (0.01 mmol) cholesterol, 13.6 mg (0.004 mmol) DSPE-PEG were added. 3400 , stirred for 12 h in the dark, chloroform was removed by rotary evaporation, and then dispersed with tetrahydrofuran. Then, it was added to secondary water under ultrasonic action, ultrasonicated for 20 min to fully hydrate it, and then nitrogen was passed to remove the residual tetrahydrofuran to finally obtain PFV-COOH / CaCO3 / PDA@PEG.

[0033] The synthesis method of the above conjugated polymer PFV-COOH is as follows:

[0034] (1) 1,6-Dibromohexane (3.8 mL, 25 mmol) and tetrabutylammonium bromide (0.17 g, 0.5 mmol) were added to a 50% KOH aqueous solution (15 mL) in sequence, heated to 75°C, and then compound 1 (0.81 g, 2.5 mmol) was added and the reaction was continued for 30 min. After the reaction was completed, the mixture was cooled to room temperature, extracted, dried, filtered, vacuum distilled, and separated by silica gel column chromatography to obtain compound 2; compound 2 (321.5 mg, 0.5 mmol) was dissolved in anhydrous N,N-dimethylformamide to dissolve it completely, and sodium azide (130 mg, 2mmol), the reaction system was heated to 85 ° C and continued to react for 20min. After the reaction was stopped, it was cooled to room temperature, extracted, dried, filtered and concentrated to obtain a crude product, which was separated by silica gel column chromatography and vacuum dried to obtain compound 3; Compound 3 (287.2 mg, 0.5 mmol) and triphenylphosphine (655.75 mg, 2.5 mmol) were added to a mixture of 5 mL of tetrahydrofuran and 1 mL of water, mixed well and stirred at room temperature overnight, and then di-tert-butyl dicarbonate (1.37 g, 6.25 mmol) was added and reacted at room temperature for 4h. After the reaction was stopped, it was extracted, concentrated and silica gel column chromatography to obtain compound 3. Compound 4; Compound 4 (251.6 mg, 0.35 mmol) was dissolved in 4 mL of dichloromethane, trifluoroacetic acid (2.6 mL, 35 mmol) was added dropwise, stirred at room temperature overnight, concentrated under reduced pressure, and then dissolved in 2 mL of methanol solution, excess sodium hydroxide solution was added, stirred for 4 h, extracted, concentrated under reduced pressure and dried in vacuo to obtain compound 5; Compound 5 (465.5 mg, 1 mmol) was dissolved in methanol, methyl acrylate (906 μL, 10 mmol) and boric acid aqueous solution (12.4 mg of boric acid was dissolved in 1.85 mL of water) were added, stirred at room temperature for 24 h, and after the reaction was completed, extracted, After drying, concentration and vacuum drying, compound 6 was obtained; 10 mL of toluene was added to a 50 mL double-necked reaction flask, followed by the addition of compound 6 (256.5 mg, 0.61 mmol) and tributyl vinyl tin (535 μL, 1.83 mmol), and after dissolution, 2,6-di-tert-butylphenol (2.5 mg, 0.012 mmol) and bis(triphenylphosphine)palladium dichloride (19.3 mg, 0.027 mmol) were added. The reaction mixture was refluxed at 100 ° C. for 8 h, cooled to room temperature, and 15 mL of 2M potassium fluoride solution was added and stirred overnight. After extraction, drying, concentration and separation by silica gel column chromatography, monomer 1-a-1 was obtained.

[0035]

[0036] (2) Monomer 1 (114 mg, 0.15 mmol), 1,4-diiodobenzene (49.5 mg, 0.15 mmol) and triethylamine (1 mL) were dissolved in N,N-dimethylformamide solution (2.0 mL) in sequence. Then, under nitrogen protection, catalysts palladium acetate (1.68 mg, 0.0075 mmol) and tri(2-methylphenyl)phosphine (10.4 mg, 0.034 mmol) were added. The reaction was vigorously stirred at 100 °C for 7.5 h. After cooling to room temperature, the polymer PFV-COOCH3 was obtained after extraction, drying, filtration and concentration. The polymer PFV-COOCH3 was directly dissolved in 10 mL of tetrahydrofuran, and sodium hydroxide aqueous solution (4 mL) was added. The mixture was stirred at 50 °C for 24 h. After the reaction was completed, the mixture was cooled to room temperature and transferred to a dialysis bag for 5 days. After dialysis, the product in the dialysis bag was freeze-dried and acidified with hydrochloric acid to obtain the conjugated polymer PFV-COOH.

[0037]

[0038] The test showed that the number average molecular weight of the obtained conjugated polymer PFV-COOH was 21903.

[0039] Example 2

[0040] The calcium carbonate-conjugated polymer composite nanoparticles of the present embodiment are based on the conjugated polymer PFV-OCH3, wrapped in a calcium carbonate nanoshell, and then modified with liposomes on its surface to form the final composite nanoparticles PFV-OCH3 / CaCO3 / PDA@PEG. The specific synthesis process is as follows: 300mg of calcium chloride dihydrate, 18mg of conjugated polymer PFV-OCH3 and 4mg of dopamine hydrochloride (PDA) are added to a beaker filled with 200mL of anhydrous ethanol and stirred to dissolve, the beaker mouth is wrapped with aluminum foil and pierced, and then the beaker is placed in a vacuum drying oven containing 20g of NH4HCO3 and reacted at 50°C for 8h. After the reaction is completed, the precipitate is collected by high-speed centrifugation (8000rpm, 10min), and the resulting precipitate is a calcium carbonate nanoparticle encapsulated with a conjugated polymer. The precipitate was ultrasonically dispersed in ethanol, 2 mL of 2 mg / mL (0.006 mmol) DOPA chloroform solution was added, and ultrasonication was continued for 20 min. Unbound DOPA was removed by centrifugation, and the precipitate was dispersed in chloroform again, and 8 mg (0.01 mmol) DPPC, 4 mg (0.01 mmol) cholesterol, 13.6 mg (0.004 mmol) DSPE-PEG were added. 3400, stirred for 12 h in the dark, chloroform was removed by rotary evaporation, and then dispersed with tetrahydrofuran. Then, it was added to secondary water under ultrasonic action, ultrasonicated for 20 min to fully hydrate it, and then nitrogen was passed to remove the residual tetrahydrofuran to finally obtain PFV-OCH3 / CaCO3 / PDA@PEG.

[0041] The synthesis method of the above conjugated polymer PFV-OCH3 is as follows:

[0042] (1) Compound (1.55 g, 3 mmol), diboronic acid pinacol ester (2.1 g, 9 mmol) and potassium acetate (3.8 g, 40 mmol) were dissolved in 1,4-dioxane (10 mL), and PdCl2(dppf) (0.27 g, 0.4 mmol) was added, and the mixture was refluxed at 100 ° C for overnight; after the reaction was completed, it was cooled to room temperature, and the reaction mixture was extracted, dried, concentrated, and then separated and purified by column chromatography, and then dried in vacuo to obtain monomer 1-a-2.

[0043]

[0044] (2) Monomer 1-a-2 (134 mg, 0.15 mmol) and p-divinylbenzene (19.5 mg, 0.15 mmol) were dissolved in N,N-dimethylformamide (2.0 mL), and triethylamine (1 mL) was added. Finally, palladium acetate (1.68 mg, 0.0075 mmol) and tri(2-methylphenyl)phosphine (10.4 mg, 0.034 mmol) were added. The mixture was stirred at 100 °C for 8 h. After the reaction was completed, it was cooled to room temperature and extracted, dried, and concentrated to obtain the conjugated polymer PFV-OCH3.

[0045]

[0046] After testing, the number average molecular weight of the obtained conjugated polymer PFV-OCH3 was 19642.

[0047] Example 3

[0048] The calcium carbonate-conjugated polymer composite nanoparticles of this embodiment are based on the conjugated polymer PFE-Br as the core, wrapped in a calcium carbonate nanoshell, and then modified with liposomes on its surface to form the final composite nanoparticles PFE-Br / CaCO3 / PDA@PEG. The specific synthesis process is as follows: 300mg of calcium chloride dihydrate, 15mg of conjugated polymer PFE-Br and 2mg of dopamine hydrochloride (PDA) are added to a beaker containing 200mL of anhydrous ethanol and stirred to dissolve. The beaker is wrapped with aluminum foil and pierced with holes, and then the beaker is placed in a vacuum drying oven containing 20g of NH4HCO3 and reacted at 40°C for 10h. After the reaction is completed, the precipitate is collected by high-speed centrifugation (8000rpm, 10min). The resulting precipitate is calcium carbonate nanoparticles encapsulating the conjugated polymer. The precipitate was ultrasonically dispersed in ethanol, 2 mL of 2 mg / mL (0.006 mmol) DOPA chloroform solution was added, and ultrasonication was continued for 20 min. Unbound DOPA was removed by centrifugation, and the precipitate was dispersed in chloroform again, and 8 mg (0.01 mmol) DPPC, 4 mg (0.01 mmol) cholesterol, 13.6 mg (0.004 mmol) DSPE-PEG were added. 3400 , stirred for 12 h in the dark, stirred for 12 h in the dark, evaporated to remove chloroform, dispersed with tetrahydrofuran, added to secondary water under ultrasonic action, ultrasonicated for 20 min to fully hydrate it, and then passed nitrogen to remove residual tetrahydrofuran to finally obtain PFE-Br / CaCO3 / PDA@PEG.

[0049] The synthesis method of the above conjugated polymer PFE-Br is as follows:

[0050] (1) Anhydrous diisopropylamine (8 mL) and compound 2 (766 mg, 1 mmol) were added to a 25 mL flask. After complete dissolution, trimethylsilylacetylene (854 μL, 6 mmol), bis-triphenylphosphine palladium dichloride (44 mg, 0.06 mmol) and cuprous iodide (24 mg, 0.12 mmol) were added. The mixture was reacted at 75°C in the dark overnight. The crude product was extracted, dried, filtered and concentrated to obtain a crude product. The crude product was purified by silica gel column chromatography to obtain compound 7. Compound 7 (290 mg, 0.42 mmol) was added to a 1:2 volume ratio of tetrahydrofuran and methanol mixed solvent (12 mL). After complete dissolution, 4 mL of 0.5 g / mL potassium carbonate aqueous solution was added and the mixture was reacted at room temperature in the dark for 5 h.

[0051] After the reaction is completed, monomer 1-b-1 is obtained through extraction, drying, concentration and silica gel column chromatography.

[0052]

[0053] (2) Monomer 1-b-1 (134 mg, 0.15 mmol) and 1,4-diiodobenzene (49.5 mg, 0.15 mmol) were dissolved in N,N-dimethylformamide solution (2 mL), and then triethylamine (1 mL), palladium acetate (1.68 mg, 0.0075 mmol) and tri(2-methylphenyl)phosphine (10.4 mg, 0.034 mmol) were added. The mixture was stirred at 100 °C for 8 h. After the reaction was completed, it was cooled to room temperature and extracted, dried, filtered and concentrated to obtain the conjugated polymer PFE-Br.

[0054]

[0055] The test showed that the number average molecular weight of the obtained conjugated polymer PFE-Br was 10388.

[0056] The microscopic morphology and comprehensive cancer treatment efficacy of PFV-COOH / CaCO3 / PDA@PEG prepared in Example 1 above were tested. The experimental process and results are as follows:

[0057] Take 10μL of PFV-COOH / CaCO3 / PDA@PEG dispersion and drop it onto the copper grid. After air drying, the microscopic morphology of the nanoparticles was observed using a transmission electron microscope. The results of the transmission electron microscope are shown in Figure 1 .Depend on Figure 1 It can be seen that the obtained PFV-COOH / CaCO3 / PDA@PEG has uniform size, an average particle size of 60±10 nm, and exhibits a core-shell structure.

[0058] The calcium ion content released by nanoparticles in solutions with different pH values was measured by atomic absorption spectroscopy. PFV-COOH / CaCO3 / PDA@PEG was dispersed in a PBS solution at pH = 8.0 to obtain a 1 mg / mL stock solution. After standing for a period of time under different pH conditions, PBS at pH = 7.4 was added to terminate the reaction. The supernatant was then centrifuged and the calcium ion content released under different pH conditions was measured. The results are shown in Figure 2. Figure 2 .Depend on Figure 2 It can be seen that with the extension of time, Ca 2+ The release of Ca 2+ The release amount reaches the maximum; as the pH of the solution decreases, Ca 2+ The release of calcium ions also gradually increases. When the pH is 5.5, the release of calcium ions reaches 80% within 4 hours. This release curve shows that PFV-COOH / CaCO3 / PDA@PEG has strong pH responsiveness.

[0059] The MTT assay was used to evaluate the cytotoxicity of PFV-COOH / CaCO3 / PDA@PEG, CaCO3 / PDA@PEG, and PFV-COOH against MCF-7 cells. The preparation of CaCO3 / PDA@PEG was similar to that of PFV-COOH / CaCO3 / PDA@PEG in Example 1, except that the conjugated polymer PFV-COOH was omitted. All other steps were identical. First, cells were seeded at a density of 8,000 cells per well in a 96-well plate and cultured until adherent. The old culture medium was then replaced with 100 μL of fresh culture medium containing varying concentrations of nanoparticles or PFV-COOH, and the cells were incubated in a CO2 incubator for 48 hours. Then, 10 μL of MTT was added to each well. After 4 hours of incubation, the culture medium was removed, and 100 μL of DMSO was added to each well. The plates were shaken for 10 minutes, and the absorbance of each well was measured at 570 nm on a microplate reader. For the phototoxicity of PFV-COOH / CaCO3 / PDA@PEG and PFV-COOH, cells were incubated with different samples for 12 h under white light (25 mW / cm 2 ) for 30 min, then continue to culture for 48 h, and finally measure cell viability using the standard MTT method. Figure 3 .like Figure 3 As shown in Figure 2, in the absence of light, the survival rate of MCF-7 cells incubated with PFV-COOH / CaCO3 / PDA@PEG (calcium ion concentration of 3.2 mM) was above 80%, indicating that PFV-COOH / CaCO3 / PDA@PEG has good biocompatibility. 2+ No significant cytotoxicity was observed in the concentration range of 0.8 to 3.2 mM, indicating that Ca 2+ Increasing concentrations did not significantly affect cell viability. Under white light irradiation, cell viability dropped to 51% at a PFV-COOH concentration of 4 μM. At the same PFV-COOH concentration, the survival rate of cells incubated with nanoparticles was only 3%. Compared to either PFV-COOH or CaCO3 / PDA@PEG alone, PFV-COOH / CaCO3 / PDA@PEG demonstrated a more significant cancer therapeutic effect by synergistically killing tumor cells through multiple pathways, including PDT, calcium overload, and mitochondrial dysfunction.

[0060] The digested 4T1 cells and MCF-7 cells were centrifuged at 1000 rpm, resuspended in serum-free medium, and the cell density was adjusted to 1×10 5 / mL. 200μL of cell suspension was added to the upper chamber of the Transwell chamber, and 600μL of complete culture medium containing 10% FBS was added to the lower chamber. PFV-COOH / CaCO3 / PDA@PEG nanoparticles with different calcium contents (0, 0.8mM, 1.6mM, 3.2mM) were added to the upper chamber of the Transwell chamber and incubated with the cells for 48h. The chamber was washed with PBS buffer solution, and the remaining non-migrated cells in the upper chamber of the Transwell chamber were carefully wiped off with a cotton swab. The cells were fixed with 4% paraformaldehyde solution for 20min, washed with PBS buffer solution, and then stained with 0.1% crystal violet solution in the dark for 10min. After staining, the excess crystal violet was washed with PBS buffer solution, and then the crystal violet was decolorized with 33% acetic acid solution. After the crystal violet was completely dissolved, the absorbance of the eluate at 570nm was measured with an enzyme marker. The experimental results are shown in Figure 4 .from Figure 4 As can be seen from the figure, when the calcium concentration of PFV-COOH / CaCO3 / PDA@PEG is 3.2mM, the migration rates of MCF-7 cells and 4T1 cells are as low as 11% and 1.8%, respectively. This experimental result shows that PFV-COOH / CaCO3 / PDA@PEG has a strong inhibitory effect on the migration of 4T1 cells and MCF-7 cells.

[0061] Prepare 20 4-week-old female BALB / c mice. 4T1 cells (1×10 6 The mice were randomly divided into five groups: PBS light group, PEG light group, CaCO3 / PDA@PEG dark group, PFV-COOH / CaCO3 / PDA@PEG dark group, and PFV-COOH / CaCO3 / PDA@PEG light group, with four mice in each group. When the tumor volume of the mice grew to 100 mm 3 At about 1 hour, the same amount of drug was injected into the tumor site of each group of mice, and the tumor volume of the mice was recorded every two days. The changes in the relative tumor volume of the mice are shown in Figure 5 .Depend on Figure 5 It can be seen that the tumor volume of mice in the PFV-COOH / CaCO3 / PDA@PEG light-irradiated group was significantly suppressed. By the 20th day, the average relative tumor volume of mice in this group was 0.05, proving that PFV-COOH / CaCO3 / PDA@PEG nanoparticles have a good anti-tumor effect under light. The mice were dissected, and the lungs of each group of mice were removed and immersed in Bouin's fixative. The number of lung metastatic nodules was recorded. The results are shown in Figure 6 .Depend on Figure 6It can be seen that a large number of lung nodules appeared in the lungs of mice in the control group (PBS illumination group and PEG illumination group), while very few lung nodules appeared in the lungs of mice in the PFV-COOH / CaCO3 / PDA@PEG illumination group, proving that PFV-COOH / CaCO3 / PDA@PEG has a good anti-tumor metastasis effect under light.

Claims

1. A calcium carbonate-conjugated polymer composite nanoparticle, characterized in that: The conjugated polymer is encapsulated by using calcium carbonate nanoshells, and liposomes are modified on the surface of the nanoshells to form the final composite nanoparticles; The conjugated polymer is 、 Any one of the following, wherein n represents the repeating unit of the monomer in the conjugated polymer, and the number average molecular weight of the conjugated polymer is 10,000 to 50,000; R is selected from and Any one of the following, m is an integer from 1 to 19, R1 represents , p is an integer from 1 to 6; R' is selected from H, 、 、 Any one of, q is an integer from 1 to 19, and R2 is selected from Br or CH3; The conjugated polymer is encapsulated in the calcium carbonate nanoshell by the gas phase diffusion method. The operation process of the gas phase dispersion method is as follows: 2+ The conjugated polymer mixed solution and ammonium bicarbonate were placed in beakers respectively and placed in a vacuum drying oven. The temperature was raised to decompose the ammonium bicarbonate into CO2 and NH3. The CO2 was then diffused into the Ca in the solution. 2+ The reaction generates a hollow calcium carbonate nanoshell, which encapsulates the conjugated polymer to obtain calcium carbonate nanoparticles encapsulating the conjugated polymer; the calcium carbonate nanoparticles containing Ca 2+ The conjugated polymer mixed solution is obtained by dissolving calcium chloride, conjugated polymer and dopamine hydrochloride in anhydrous ethanol; The method for modifying liposomes on the surface of nanoshells is as follows: calcium carbonate nanoparticles encapsulating conjugated polymers are ultrasonically dispersed in ethanol, and then a chloroform solution of 1,2-dioleoyl-sn-glycero-3-phosphate sodium salt is added, ultrasonicated for 15 to 30 minutes, and then dispersed in chloroform after centrifugation. 1,2-dipalmitoyl-sn-glycero-3-phosphocholine, cholesterol and distearoylphosphatidylethanolamine-polyethylene glycol 3400 are added, and stirred for 12 to 15 hours under dark conditions. After removing the chloroform, the nanoparticles are dispersed with tetrahydrofuran, added to secondary water under ultrasonication, and ultrasonicated for 15 to 30 minutes to fully hydrate them. Finally, the residual tetrahydrofuran is removed to obtain calcium carbonate-conjugated polymer composite nanoparticles.

2. The calcium carbonate-conjugated polymer composite nanoparticles according to claim 1, wherein: The mass ratio of the calcium chloride, the conjugated polymer and dopamine hydrochloride is 300:10-20:1-5.

3. The calcium carbonate-conjugated polymer composite nanoparticles according to claim 1, wherein: Raise the temperature to 30-60°C to decompose ammonium bicarbonate into CO2 and NH3. The reaction lasts for 5-20 hours, and the CO2 reacts with the Ca in the solution. 2+ The reaction generates hollow calcium carbonate nanoshells that encapsulate the conjugated polymer.

4. The calcium carbonate-conjugated polymer composite nanoparticles according to claim 1, wherein: The molar ratio of the 1,2-dioleoyl-sn-glyceryl-3-phosphate sodium salt, 1,2-dipalmitoyl-sn-glycerol-3-phosphocholine, cholesterol and distearoylphosphatidylethanolamine-polyethylene glycol 3400 is 1-3:3:1-4:1-3, wherein the mass ratio of the 1,2-dioleoyl-sn-glyceryl-3-phosphate sodium salt to the conjugated polymer in the calcium carbonate nanoparticles encapsulating the conjugated polymer is 4:15-22.

5. The calcium carbonate-conjugated polymer composite nanoparticles according to claim 1, wherein: The particle size of calcium carbonate-conjugated polymer composite nanoparticles is 30 to 200 nm.

6. Use of the calcium carbonate-conjugated polymer composite nanoparticles according to any one of claims 1 to 5 in the preparation of anti-tumor and anti-tumor metastasis drugs.